2000
DOI: 10.1081/ma-100101120
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transfer Catalyzed Free Radical Polymerization: Kinetics of Polymerization of Alkyl Methacrylates Using Potassium Peroxomonosulphate/Tetrabutyl Phosphonium Chloride Catalyst System

Abstract: The kinetics of phase transfer catalyzed free radical polymerization of alkyl methacrylates (MMA and EMA) using potassium peroxomonosulphate (water-soluble initiator) coupled with phase transfer catalyst viz., tetrabutylphosphonium chloride (TBPC) have been investigated in ethylacetate-water biphase system at 50 ± 0.1°C. The rate of polymerization increased with an increase in the quaternary salt concentration, but showed a tendency to level off at a higher concentration. An increase in peroxomonosulphate conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…3). Similar order of reaction with respect to initiator concentration has been reported for the polymerization of other vinyl monomers [29,31,32,40] using different phase transfer catalyst initiated by PDS. The higher order of polymerization in the case of initiator variation may be either due to gel effect or diffusion-controlled termination rate constant [40].…”
Section: Effect Of [Pds] On the Rate Of Polymerization (R P )mentioning
confidence: 48%
“…3). Similar order of reaction with respect to initiator concentration has been reported for the polymerization of other vinyl monomers [29,31,32,40] using different phase transfer catalyst initiated by PDS. The higher order of polymerization in the case of initiator variation may be either due to gel effect or diffusion-controlled termination rate constant [40].…”
Section: Effect Of [Pds] On the Rate Of Polymerization (R P )mentioning
confidence: 48%
“…In case, if the termination takes place by combination of primary radicals, the initiator order is expected to deviate from half order. However, in this study, the initiator order was found to be greater than half and it may be attributed to gel effect or diffusion-controlled termination constant [41].…”
Section: Role Of [Mma] On the Rate Of Polymerization (R P )mentioning
confidence: 78%
“…The higher initiator order can be explained by gel effect or diffusion controlled termination constant [23]. In addition, higher order of initiator concentration suggests that the termination is bimolecular and monomer-induced decomposition of PDS was absent [23]. The greater than half order with respect to initiator concentration was reported in phase-catalyzed polymerization systems [36][37][38][39].…”
Section: Variation Of [Pds] On the R Pmentioning
confidence: 92%
“…4a, b). The higher initiator order can be explained by gel effect or diffusion controlled termination constant [23]. In addition, higher order of initiator concentration suggests that the termination is bimolecular and monomer-induced decomposition of PDS was absent [23].…”
Section: Variation Of [Pds] On the R Pmentioning
confidence: 99%